ANALYZING SYLLABUS’ LEARNING OBJECTIVES IN THE LESSON PLAN - Rizki Widiastuti; Syafryadin Syafryadin; Istiqomah Nur Rahmawati (Universitas Galuh, 2021)
Introduced to relatively new curriculum, KTSP, teachers are given the challenge to develop the curriculum, the syllabus, the lesson plan and the activities in the classroom, yet the teachers seem still have the difficulties in developing the curriculum, integrating the learning objectives in the syllabus into activities lay in lesson plan thus this study is conducted in purpose to find out how teachers interpret the learning objectives in syllabus into the lesson plan, discover the difficulties and how the teachers overcome the difficulties. Qualitative-Descriptive design was used in conducting the study. Therefore, two second-grade English teachers in one of private high school in Bandung are selected to be the subject of this study. The data was gained and analyzed from document analysis and interview. The study found that teachers using the existed syllabus and lesson plan, which can be provided by school or available on the internet. They do not modify or revise the syllabus; they use it as guidance for their teaching. They modify the lesson plan by seeing the condition of the class and students’ character without stating it into formal form of lesson plan. Yet the teachers are able to interpret and implement the objectives in the syllabus into learning activities well and create the appropriate situation in the classroom. The difficulties faced by the teachers are mainly because they are inexperienced teachers, with relatively short period of time they are still in the process of recognizing and understanding the surroundings, relate to the aspects within the school, students and curriculum itself. Sharing and learning from the experienced-teachers may be the best solution of the problem. The coordination and collaboration among teachers in school and between teachers and school may give benefit also in reaching the expected learning objectives and developing the KTSP curriculum. Keywords: curriculum, KTSP, lesson plan, qualitative-descriptive, syllabus.